Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1039/c6ra14190k
|View full text |Cite
|
Sign up to set email alerts
|

Non-isothermal crystallization kinetics, thermal degradation behavior and mechanical properties of poly(lactic acid)/MOF composites prepared by melt-blending methods

Abstract: In this article, poly(lactic acid)/metal–organic framework composites were prepared by melt-blending method and the effects of MOFs on the non-isothermal crystallization, thermal degradation and mechanical property of poly(lactic acid) were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 55 publications
1
29
0
1
Order By: Relevance
“…The same enhancing effect can be observed in 50% mass loss (T 50 ). On the contrary, the maximum mass loss (T max ) are declined at all range of fillers loadings, which indicate that MOFs improve the thermal stability at the high‐temperature region (370 o C‐550 o C) …”
Section: Resultsmentioning
confidence: 97%
“…The same enhancing effect can be observed in 50% mass loss (T 50 ). On the contrary, the maximum mass loss (T max ) are declined at all range of fillers loadings, which indicate that MOFs improve the thermal stability at the high‐temperature region (370 o C‐550 o C) …”
Section: Resultsmentioning
confidence: 97%
“…Based on the differential thermogravimetric profiles, they observed that onset of thermal degradation of PLLA dropped from 270 to 180 and 210 °C for PLLA‐5% CaO and PLLA‐5% MgO systems, respectively. Dai et al . fabricated PLA composites with Zn (II)‐pyridine 2,5‐dicarboxylate MOF.…”
Section: Resultsmentioning
confidence: 99%
“…They also observed decreased thermal stability of PLA at elevated tempeartures, which was ascribed to unzipping depolymerization. On the other hand, the degradation of PLA has been reported to be a complex phenomenon due to random scissions leading to linear and cyclic oligomers, which can potentially recombine leading to complex byproducts …”
Section: Resultsmentioning
confidence: 99%
“…[31][32][33] Unlike the direct catalytic conversion of sugars into LA derivatives or the development of MOF-PLA composites, the challenging separationo fL Af rom fermentation brothsh as surprisingly not yet been addressed by the MOF community. [34,35] Here we propose ap rocess in which the combination of adsorption on aM OF and reactive desorption allows the gypsum-free recovery of LA (Figure 1, green).…”
Section: Introductionmentioning
confidence: 98%
“…As reviewed by our group, initial studies focused on the separation of petrochemicals in apolar backgrounds, but attention moved to the separation of complex (e.g., chiral) compounds and to the isolation of bio‐based compounds from aqueous media . Unlike the direct catalytic conversion of sugars into LA derivatives or the development of MOF–PLA composites, the challenging separation of LA from fermentation broths has surprisingly not yet been addressed by the MOF community . Here we propose a process in which the combination of adsorption on a MOF and reactive desorption allows the gypsum‐free recovery of LA (Figure , green).…”
Section: Introductionmentioning
confidence: 99%